Galaxy And Mass Assembly (GAMA): the bright void galaxy population in the optical and mid-IR. Issue 4 (9th September 2015) - Penny, S. J.; Brown, M. J. I.; Pimbblet, K. A.; Cluver, M. E.; Croton, D. J.; Owers, M. S.; Lange, R.; Alpaslan, M.; Baldry, I.; Bland-Hawthorn, J.; Brough, S.; Driver, S. P.; et al.
Abstract: We examine the properties of galaxies in the Galaxies and Mass Assembly (GAMA) survey located in voids with radii >10 h −1 Mpc. Utilizing the GAMA equatorial survey, 592 void galaxies are identified out to z ≈ 0.1 brighter than M r = −18.4, our magnitude completeness limit. Using the W Hα versus [N ii ]/Hα (WHAN) line strength diagnostic diagram, we classify their spectra as star forming, AGN, or dominated by old stellar populations. For objects more massive than 5 × 10 9 M⊙, we identify a sample of 26 void galaxies with old stellar populations classed as passive and retired galaxies in the WHAN diagnostic diagram, else they lack any emission lines in their spectra. When matched to Wide-field Infrared Survey Explorer mid-IR photometry, these passive and retired galaxies exhibit a range of mid-IR colour, with a number of void galaxies exhibiting [4.6] − [12] colours inconsistent with completely quenched stellar populations, with a similar spread in colour seen for a randomly drawn non-void comparison sample. We hypothesize that a number of these galaxies host obscured star formation, else they are star forming outside of their central regions targeted for single-fibre spectroscopy. When matched to a randomly drawn sample of non-void galaxies, the void and non-void galaxies exhibit similar properties in terms of optical and mid-IR colour, morphology, and star formation activity, suggesting comparable mass assembly and quenching histories. A trend in mid-IR [4.6] − [12] colour is seen, such that both void and non-void galaxies with quenched/passive colours <1.5 typically have masses higher than 10 10 M⊙, where internally driven processes play an increasingly important role in galaxy evolution.